THE DIFFERENTIAL CRITERION IN THE FRETTING PHENOMENON - Ştefan GHIMISI (Fiabilitate şi Durabilitate)
Fretting is now fully identified as a small amplitude oscilatory motion which induces a harmonic tangential force between two surfaces in contact. It is related to three main loadings,i.e. fretting-wear,fretting-fatigue and fretting corrosion. This papers proposes several criteria to determine the transition between partial slip and gross slip. A theoretical expression of the transition depending on the applied normal force and the tangential displacement will be introduced in order to plot fretting maps. Two different expresions are introduced for each of these functions depending on the sliding condition. Demonstration will only be given in the case of partial slip and for the force approach.